Proposed new interior design for Healthy Product Organics Cafe of Healthy Paradise Sdn Bhd at K-09-12, No. 1, Jalan Solaris, Solaris Mont’ Kiara, 50480, Kuala Lumpur / Muhammad Farid Hilmi Sholikhin - Sholikhin, Muhammad Farid Hilmi (Faculty of Architecture, Planning and Surveying, 2010)
The title of mny project study is proposed new interior design for Healthy Product Organics Cafe of Healthy Paradise Sdn Bhd at K-09- 12, No.1, Jalan Solaris, Solaris Mon’t Kiara,50480, Kuala Lumpur. It is located at Jalan Solaris in SohoKL. It is a good spot to build up a new cafe using healthy and organic products because there are a lot of already famed and established cafe.The target market of this healthy organics product is mostly people who are aware about what they eat and concern for their health. It is basically focusing on more than one type of target market since disease attacks the health of (people without age limits. It is also one effective way to spread the awareness of eating healthy and organic food. The first branch cafe from the product at Petaling Jaya is one of the way for the company to expand their target market and business. The main objective of this project is to portray a new look for the product and the cafe. In other way, indirectly change the perception of how people take their meal throughout their life. There are a few of methodologies and techniques have been used to achieve this objective. There three phase for each methodology. It depends on how cooperative the client and how we strive for the information to be included in this report.The cafe needs a new concept and images that shows the looks of a healthy, revitalize cafe. It is key important to give a better images for this cafe referring back to the main objective of this proposal yet to improvise the products marketing strategies.